Assessment of CDA and Morphlink-C Algorithms method in crack detection using [Multirotor DJ1 phantom 3] image / Muhammad Hafizi Abd Rahaim - Abd Rahaim, Muhammad Hafizi (2018)
The crack or facade on the building was frequently occurred where there are could bring the hazard to the people around the building. The crack also consumed a lot of construction fees to always be maintenance for long time. Unmanned Aerial Vehicle was used in various application, the technology that comes that have used in various application of disaster occurrence. Caused by the autonomous of the controlling method, the UAV was often used in monitor the building fa9ade such as crack. With have of certain distance, the UAV can could pretend the safety of the technician and avoid any hazards. This paper was discussed about the application of UAV in crack detection by capturing the image of the damaged area. Then, the image was being processed in the photogrammetry software to produce the orthomosaic and point cloud data. These data model then was evaluated their availability of processed image to detect crack using CDA and MorphLink-C algorithms. From the result obtained, it was shows that, MorphLink-C was seems to be distinguished the crack on the building wall.